The scholar versus the pagan on Greencraft tree walks - Van Gulik, Léon A. (Traditiones (Ljubljana), 2012)
This article offers an ethnography of a tree walk ritual of the Belgian Greencraft Wicca movement. The description is employed to discuss the notions of reflexivity, reactivity, and the double hermeneutic. By interpreting the data, the author concludes that the double hermeneutic is a problem of different contexts rather than between different groups. Attunement and suspension of disbelief are singled out as means to overcome misunderstandings between the scholar and the researched.
Keywords: ethnology; Etnologija; customs; Šege; Rituali; Belgija; Hermenevtika; Verovanje; Obredi; rituals; hermeneutics; ljudska verovanja; ljudski obredi; ljudski običaji